Pengaruh Dialek terhadap Fonetik Bahasa Indonesia - Annisa Harahap; Azzam Al Fatih (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Indonesian, as a unified language, has a wealth of dialects which are influenced by various regional languages. These dialect differences significantly influence the phonetic aspects of Indonesian, especially in terms of sound pronunciation. This research aims to examine how dialect variations can change the way speakers pronounce words in Indonesian.Analysis of various dialects in Indonesia shows that there are quite striking differences in terms of phoneme use, intonation and rhythm. Factors such as mother tongue, social environment, and level of education also influence pronunciation variations. Some examples of dialect influences include changes in consonant or vowel sounds, addition or deletion of syllables, and differences in intonation which can change the meaning of a sentence.This research has important implications in the fields of linguistics, sociolinguistics, and language education. A deeper understanding of the influence of dialect on Indonesian phonetics can help in developing a more relevant and effective Indonesian language learning curriculum, as well as in increasing awareness of the richness of Indonesian language and culture.